2021
DOI: 10.1002/cbdv.202100520
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese Medicine Ganshuang Granules Attenuate CCl4‐Induced Hepatic Fibrosis by Modulating Gut Microbiota

Abstract: Gut dysbiosis contributes to hepatic fibrosis. Emerging evidence revealed the major role of traditional Chinese medicine (TCM) in gut microbiota homeostasis. Here, we aimed to investigate the anti-fibrotic activity and underlying mechanism of ganshuang granules (GS), particularly regarding gut microbiota homeostasis. CCl 4induced hepatic fibrosis models were allocated into 4 groups receiving normal saline (model), 1.0, 2.0, or 4.0 g/ kg GS for 5 weeks. As result, GS treatment alleviated liver injury in CCl 4 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…For example, Xiaoyaosan decoction, containing eight Chinese herbs, was reported to prevent the progression of liver fibrosis induced by CCl 4 in rats, which was mediated through transforming growth factor beta1 (TGFβ1)/Smad signaling cascades (Zhou et al, 2021). Ganshuang granules, a prepared TCM decoction, can regulate gut microbiota composition and diversity to maintain intestinal integrity and exert antioxidant and anti-inflammatory effects, therefore repressing liver fibrosis (Zhao et al, 2021). Yiguanjian decoction, a representative TCM comprising six medicinal herbs, inhibits liver fibrosis by maintaining the resting state of hepatic stellate cells and hepatocyte viability (Li et al, 2019), repressing liver angiogenesis (Zhou et al, 2015), and modulating inflammatory cytokine release from macrophages .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Xiaoyaosan decoction, containing eight Chinese herbs, was reported to prevent the progression of liver fibrosis induced by CCl 4 in rats, which was mediated through transforming growth factor beta1 (TGFβ1)/Smad signaling cascades (Zhou et al, 2021). Ganshuang granules, a prepared TCM decoction, can regulate gut microbiota composition and diversity to maintain intestinal integrity and exert antioxidant and anti-inflammatory effects, therefore repressing liver fibrosis (Zhao et al, 2021). Yiguanjian decoction, a representative TCM comprising six medicinal herbs, inhibits liver fibrosis by maintaining the resting state of hepatic stellate cells and hepatocyte viability (Li et al, 2019), repressing liver angiogenesis (Zhou et al, 2015), and modulating inflammatory cytokine release from macrophages .…”
Section: Introductionmentioning
confidence: 99%
“…A TCM composed of Gardeniae Fructus and Semen Sojae Praeparatum, named Zhizichi Decoction, was found to reduce liver injury by regulating the gut microbiota population, promoting butyric acid production and activating the antioxidant reaction ( 48 ). In addition, Ganshuang Granules [composed of Chinese herbs such as Radix Codonopsis, Bupleurum Falcatum and Salviae Miltiorrhiza] can rebalance the gut microbiota and reduce intestinal permeability, thereby reducing oxidative stress and inflammation and ultimately ameliorating CCl 4 -induced hepatotoxicity and ALI ( 49 ). At present, the potential roles of these agents based on gut microbiota in alleviating hepatotoxicity and ALI have been constantly explored, which not only provides a promising target for the prevention and treatment of the disease but also deepens the awareness of the important research value of TCMs and NPs in disease treatment.…”
Section: Targeting Gut Microbiota For Acute Liver Injurymentioning
confidence: 99%
“…The formula contains 13 herbs, such as Bupleuri Radix , Angelicae Sinensis Radix , Poria, and Salviae Miltiorrhizae Radix et Rhizoma , which have good therapeutic effects on clinical acute and chronic hepatitis and liver cirrhosis ( Shi et al, 2017 ; Zeng et al, 2020 ; Lu et al, 2021 ). Modern pharmacological studies indicated that GSG can regulate the intestinal microbiota and moderate CCl4-induced liver fibrosis ( Zhao et al, 2021 ). In addition, GSG can slow the progression of liver fibrosis by impeding mTOR-autophagy to inhibit the activation of hepatic stellate cells (HSCs) ( Shi et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%